Langit-Langit Manusiawi: Teknologi dan Kecerdasan Emosional dalam Strategi Diferensiasi Hotel Butik - Ahmad Nurcahyadi Kusuma (Journal of Management and Creative Business, 2026)
This article introduces the Human Ceiling as a conceptual framework for boutique hotel differentiation strategy. The research aim is to describe the floor-ceiling dynamic in hospitality operations, where operational technology establishes the performance floor while emotional intelligence and organisational core values determine the ceiling of guest experience quality. A qualitative reflective case study methodology based on a practitioner-researcher position was employed. Data were collected from practitioner observation, guest reviews from five OTA platforms, and Booking.com sub-score data as a structured analytical unit. Chesa Canggu, a 36-room boutique hotel in Canggu, Bali, was selected as a purposive illustrative case. Results show that the Staff dimension achieves a perfect 10.0 in a property with a high operational floor (Cleanliness 9.9, Facilities 9.8, Comfort 9.8, Location 9.8), consistent with the framework's prediction. Cross-property validation using data from ten boutique hotels in the Canggu area confirms that a positive difference between Staff scores and average floor dimensions is found across all properties, strengthening the generalisability of the pattern. The Hospitality Integration Model is introduced with four dimensions: System Intelligence, Commercial Awareness, Human Leadership, and Cultural Relevance. Limitations include reliance on the reflective methodology requiring cross-case verification.